2010
DOI: 10.1029/2009jd012529
|View full text |Cite
|
Sign up to set email alerts
|

Meridional distribution of molecular hydrogen and its deuterium content in the atmosphere

Abstract: The atmospheric molecular hydrogen concentration and its deuterium abundance were measured in remote air samples collected onboard six Pacific Ocean ship transects between 37°N and 77°S during years 2001 through 2005. The data reveal a year‐round interhemispheric gradient in H2 concentration and isotopic composition with the extratropical Northern Hemisphere lower in H2 concentration by 17 ± 11 ppb and δD of H2 by 16 ± 12‰ than the Southern Hemisphere (95% confidence). On the basis of these snapshots, the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 38 publications
(111 reference statements)
1
40
2
Order By: Relevance
“…Recently, isotope effects in the production processes of H 2 have been studied (Gerst and Quay, 2001;Rahn et al, 2002bRahn et al, , 2003Röckmann et al, 2003;Rhee et al, 2006a;Feilberg et al, 2007;Rhee et al, 2008;Röckmann et al, 2010a,b;Vollmer et al, 2010;Walter et al, 2011;Haumann et al, 2012), as well as the isotope effects in the H 2 uptake by soils (Gerst and Quay, 2001;Rahn et al, 2002a;Rice et al, 2011). Two chemical transport models have been adapted to incorporate the stable isotopic composition of H 2 , namely GEOS-CHEM (Price et al, 2007) and TM5 (Pieterse et al, 2009(Pieterse et al, , 2012, and many more δD data have become available for the validation of such models (Rice et al, 2010;Batenburg et al, 2011). However, for obvious practical reasons, most of these data were collected at ground level, and yield little information about processes higher up in the atmosphere, particularly in the Upper TroposphereLower Stratosphere (UTLS) region.…”
Section: Stable Isotope Studies Of Hmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, isotope effects in the production processes of H 2 have been studied (Gerst and Quay, 2001;Rahn et al, 2002bRahn et al, , 2003Röckmann et al, 2003;Rhee et al, 2006a;Feilberg et al, 2007;Rhee et al, 2008;Röckmann et al, 2010a,b;Vollmer et al, 2010;Walter et al, 2011;Haumann et al, 2012), as well as the isotope effects in the H 2 uptake by soils (Gerst and Quay, 2001;Rahn et al, 2002a;Rice et al, 2011). Two chemical transport models have been adapted to incorporate the stable isotopic composition of H 2 , namely GEOS-CHEM (Price et al, 2007) and TM5 (Pieterse et al, 2009(Pieterse et al, , 2012, and many more δD data have become available for the validation of such models (Rice et al, 2010;Batenburg et al, 2011). However, for obvious practical reasons, most of these data were collected at ground level, and yield little information about processes higher up in the atmosphere, particularly in the Upper TroposphereLower Stratosphere (UTLS) region.…”
Section: Stable Isotope Studies Of Hmentioning
confidence: 99%
“…Not only are some altitudes underrepresented in the published δD data, also some regions of the world are not well covered. Previously published data were mostly from samples collected at two stations at the west coast of North America and on Pacific Ocean transects (Gerst and Quay, 2000;Rice et al, 2010), or at stations in Europe and the polar regions . Data from other regions, such as South Asia, are scarce.The aim of analyzing data from the CARIBIC program is to close both the altitudinal and the regional gap in the observations.…”
Section: A M Batenburg Et Al: δD(h 2 ) In the Tropopause Region 4635mentioning
confidence: 99%
“…The δD soil values (−629 to −451 ‰) shown in Table 2 are less depleted than the H 2 in isotopic equilibrium with water (≈ −700 ‰). Previous observations from environmental H 2 production yielded a δD of −628 ‰ for two seawater samples (Rice et al, 2010), −778 ‰ for a termite headspace sample and −690 ‰ for two headspace samples from a eutrophic water pond (Rahn et al, 2002b). Kawagucci et al (2010) proposed that microbiological H 2 consumption and production could destroy the thermal isotopic equilibrium between H 2 and H 2 O in low-temperature hydrothermal fluids.…”
Section: δD Of H 2 Emitted From the Soilmentioning
confidence: 99%
“…The δD values are usually given in per mill (‰). Recent studies showed that the global mean δD value of atmospheric H 2 is about +130 ‰ Quay, 2000, 2001;Rice et al, 2010).…”
Section: Q Chen Et Al: Isotopic Signatures Of Production and Uptakementioning
confidence: 99%
“…Tropospheric H 2 is enriched in deuterium with δD ∼ +130 ‰, (Gerst and Quay, 2001;Rhee et al, 2006;Rice et al, 2010;Batenburg et al, 2011) compared to surface emissions from fossil fuel combustion and biomass burning (δD approximately −200 ‰ and −300 ‰, respectively) (Gerst and Quay, 2001;Rahn et al, 2002;Röckmann et al, 2010a;Vollmer et al, 2010). As originally proposed by Gerst and Quay (2001) from budget closure, the photochemical sources of H 2 are also enriched in deuterium with δD between ∼ +100 ‰ and +200 ‰, (Rahn et al, 2003;Röckmann et al, 2003Röckmann et al, , 2010bFeilberg et al, 2007;Nilsson et al, 2007Nilsson et al, , 2010Pieterse et al, 2009 (Novelli et al, 1999;Hauglustaine and Ehhalt, 2002;Ehhalt and Rohrer, 2009;Pieterse et al, 2011) the extreme deuterium depletion relative to ambient atmospheric H 2 makes it a quite important contributor to the isotope budget (Price et al 2007;Pieterse et al 2011).…”
Section: Abstract Biologically Produced Molecular Hydrogen (H 2 )mentioning
confidence: 99%